Enhancing the Stability of Light-Responsive Automatic Door Systems Against Sudden Light Changes - Çevik, Hasan Hüseyin; Uyar, Okan (Transpublika Publisher, 2025)
In this study, a low-cost and light-responsive automatic chicken coop door system was developed. The system was designed to operate stably under sudden changes in ambient light conditions. The system was designed to address instability issues commonly encountered in coop doors that are required to open and close based on daylight conditions. For this purpose, a light testing cabinet was constructed and various illumination levels were tested using LDR and BH1750 light sensors along with optical diffusers. Regression models were developed to convert the analog data from the LDR circuit into lux values. Moreover, statistical filtering methods such as the Interquartile Range (IQR) and Z-Score were applied to prevent system instability caused by sudden changes in lighting (e.g., vehicle headlights, passing clouds). The effectiveness of the filtering methods was analyzed using both artificially generated data from the light test cabinet and real minute-based solar irradiance data collected from a meteorological station. The developed system achieved enhanced sensor accuracy and operational stability through the use of low-cost components and the integration of an outlier detection module. Test results showed that the regression model used for lux estimation based on LDR readings achieved an R² value of 0.97, and the application of IQR and Z-Score filtering methods successfully removed outliers, resulting in improved operational stability under variable lighting conditions. The proposed approach offers a versatile solution for various sensor-driven control systems, including automatic doors and smart home applications.